Estudo do efeito da inativação fotodinâmica na transferência de resistência bacteriana - Lima, Rebeca Vieira de (Universidade Federal de São Carlos, 2023)
Gram-negative bacteria are relatively more resistant and difficult to treat because they have a larger outer membrane than Gram-positive bacteria and several resistance mechanisms. In addition, they are of great clinical importance because they cause several infections in humans. There are estimates that, in a few years, resistant microorganisms may become the leading cause of death worldwide, surpassing deaths caused by cancer, diabetes and even traffic accidents, thus being an urgent issue on a global scale. Photodynamic inactivation (PDI) is an advantageous technique for reducing microorganisms that presents itself as a promising alternative to avoid antibiotics, for example, by being able to break bacterial resistance and make acquired resistance impossible. Thus, this study aimed to attenuate or inhibit the transfer of bacterial resistance in resistant strains. In this way, it was possible to evaluate the behavior of clinically relevant Gram-negatives, Klebsiella pneumoniae and Escherichia coli, after treatment with PDI using dose light of 30 J/cm2 and curcumin as photosensitizer (PS) and thus to understand through logistic modeling of the growth curves how PDI was able to affect the characteristic bacterial behavior. Furthermore, in an effort to establish conditions leading to the goal it was observed that with the methodology made there was interference in the photodynamic action mediated by sodium dodecyl sulfate (SDS), which resulted in low photodynamic inactivation and alteration of the minimum inhibitory concentration (MIC) of these strains. In general, these are severely difficult bacteria to treat and it was seen that all the elements used in the PDI (PS, light, SDS) affected the bacteria, requiring further studies to investigate the best approach for these Gram-negative bacteria and to verify if there is an alteration with external molecules such as SDS.
Study of the effect of photodynamic inactivation in the transfer of bacterial resistance
Keywords: Photodynamic inactivation; Bacterial strain; Resistance; SDS; Klebsiella pneumoniae; CIENCIAS DA SAUDE